Characterization of Immunophenotype and Differentiation Potential of Human Bone Marrow Mesenchymal Stromal Cells after Cryopreservation - Petrenko, Yu. A.; Skorobogatova, N. G.; Volkova, N. A.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2011)
Stromal cells derived from adult human bone marrow (BM) after in vitro expansion demonstrate a specific immunophenotype and ability to multilineage differentiation, inherent to mecenchymal stromal cells (MSCs)m. It was established that cryopreservation of human BM MSCs by two-step freezing under protection of 10% DMSO enables to preserve their immunophenotype and ability to induced osteogenic and adipogenic differentiation in vitro.